International Standards of the IMRaD Structure in Academic Writing: Principles, Applications, and Global Publishing Norms (Journal of Pedagogical Inventions and Practices, 2026)
The IMRaD structure—Introduction, Methods, Results, and Discussion—is the most widely adopted organizational framework in scientific and academic writing. It is recognized as an international standard for presenting empirical research in journals indexed in Scopus, Web of Science, and other global databases. This article examines the international standards of the IMRaD structure, its historical development, disciplinary applications, and editorial requirements across leading academic publishers. The study analyzes how IMRaD enhances clarity, transparency, reproducibility, and scientific communication. It also explores variations of IMRaD across disciplines, journal-specific guidelines, and reporting standards such as CONSORT, PRISMA, and APA recommendations. Furthermore, the article discusses challenges in applying IMRaD in interdisciplinary and qualitative research. The findings indicate that adherence to IMRaD standards significantly increases publication quality, peer-review success, and international research visibility. The article concludes that IMRaD remains a universal benchmark for scientific communication in the global academic community